IMPLEMENTATION OF A HOTS-BASED PROJECT BASED LEARNING (PjBL) MODEL TO IMPROVE MATHEMATICAL LITERACY OF SENIOR HIGH SCHOOL STUDENTS - Weni Widya Asriati; Tesi Kumalasari; Rogerio Beguiristen (Program Studi Pendidikan Matematika, Universitas Bina Bangsa Getsempena, 2025)
This study aims to develop a Project Based Learning (PjBL) model integrated with Higher Order Thinking Skills (HOTS) and the scientific approach to enhance high school students’ mathematical literacy skills. The research employed a research and development (R&D) design based on the Dick & Carey model. The participants were 32 eleventh-grade students at SMA Dharma Pancasila Medan, selected using total sampling. Research instruments included expert validation sheets, mathematical literacy tests, student response questionnaires, observation sheets, and interviews. Expert validation results indicated that the developed learning model was highly valid with an average score of 89.7%. The implementation results revealed a significant improvement, with students’ average pre-test scores increasing from 51.4 to 83.5 in the post-test, and a gain score of 0.66 categorized as moderate–high. Indicators of mathematical literacy, namely formulating situations mathematically, employing concepts, facts, procedures, and reasoning, and interpreting and evaluating outcomes, all showed significant improvements. Students’ responses to the learning model were highly positive, with more than 87% stating that the learning process was more engaging, facilitated concept understanding, and enhanced critical thinking and collaboration skills. Therefore, the PjBL-based HOTS model integrated with the scientific approach has been proven effective in improving students’ mathematical literacy while supporting the achievement of 21st-century competencies and the Sustainable Development Goal 4: Quality Education.